Endoscopic Treatment of Enterocutaneous Fistulas in Crohn's Disease. Issue 5 (6th April 2022) - Yzet, Clara; Brazier, Franck; Sabbagh, Charles; Le Mouel, Jean-Philippe; Hakim, Sami; Nguyen-Khac, Eric; Fumery, Mathurin
Abstract : BACKGROUND: Management of enterocutaneous fistulas in Crohn's disease is challenging. Most patients still need intestinal resection in the biologic era. OBJECTIVE: The aim of this study was to evaluate the efficacy of endoscopic treatment for enterocutaneous fistulas. DESIGN: This is a retrospective study of medical records. SETTINGS: This study was conducted in a single institution. PATIENTS: All consecutive patients with Crohn's disease with an enterocutaneous fistula who underwent endoscopic fistula closure with the use of an over-the-scope clip or a hemostatic clip were included. MAIN OUTCOME MEASURES: The main outcome measured was the clinical success 3 months after the procedure, which was defined as the complete closure of all fistulas at physical examination and complete cessation of the drainage from the external opening, without surgery. RESULTS: Eight patients (men, 25%; median age 45 years [interquartile range, 33–51]) were followed. Fistulas were localized at the ileocolonic or colocolonic anastomosis in 7 patients and at the stomach in 1 patient. Seven patients were treated with an over-the-scope clip, and one was treated with a hemostatic clip. Technical success was achieved in all cases. Clinical success at 3 months was achieved in 75% of cases (6/8 patients). After a median 16-month (interquartile range, 13–23) follow-up, 3 of 8 (37.5%) patients had enterocutaneous fistula closure and 2 of 8 (25%) needed intestinal resection. No complications were observed. LIMITATIONS: The retrospective nature, the small sample size of the study, and the heterogeneity of the population limit the interpretation of the results. CONCLUSIONS: Endoscopic treatment of enterocutaneous fistulas is feasible with a short-term effectiveness. Additional studies are needed to confirm these results. See Video Abstract at http://links.lww.com/DCR/B614 . TRATAMIENTO ENDOSCÓPICO DE FÍSTULAS ENTEROCUTÁNEAS EN ENFERMEDAD DE CROHN: ANTECEDENTES: Es desafiante el manejo de las fístulas enterocutáneas en enfermedad de Crohn. En la era biológica, la mayoría de los pacientes todavía requieren de resección intestinal. OBJETIVO: Evaluar la eficacia por tratamiento endoscópico de fístulas enterocutáneas. ENTORNO CLINICO: Estudio retrospectivo de registros médicos. AJUSTE: Realizado en una sola institución. PACIENTES: Se incluyeron todos los pacientes consecutivos con fístula enterocutánea en enfermedad de Crohn, sometidos a cierre endoscópico de la fístula con clip sobre el endoscopio o clip hemostático. PRINCIPALES MEDIDAS DE VALORACION: El éxito clínico a los 3 meses después del procedimiento. Definido al examen físico, como el cierre completo de todas las fístulas y cese completo del drenaje por la abertura externa, sin cirugía. RESULTADOS: Se estudiaron a ocho pacientes (hombres, 25%, mediana de edad de 45 años (rango intercuartílico, 33-51)). En 7 pacientes, las fístulas se localizaron en la anastomosis ileocolónica o colocolónica y un paciente, en el estómago. Siete pacientes fueron tratados con clip sobre el endoscopio y uno con clip hemostático. Se logró éxito técnico en todos los casos. Se logró éxito clínico a los 3 meses en 75% de los casos (6/8 pacientes). Después de una mediana de 16 meses (rango intercuartílico, 13-23), de seguimiento 3/8 (37, 5%) pacientes presentaron cierre de fístulas enterocutáneas y 2/8 (25%) requirieron resección intestinal. No se observaron complicaciones. LIMITACIONES: Estudio retrospectivo, pequeño tamaño de la muestra y heterogeneidad de la población, limitaron la interpretación de los resultados. CONCLUSIONES: Es posible el tratamiento endoscópico de fístulas enterocutáneas con efectividad a corto plazo. Se requieren nuevos estudios para confirmar estos resultados. Consulte Video Resumen en http://links.lww.com/DCR/B614 . (Traducción—Dr. Fidel Ruiz Healy )